Characterisation of enterococci strains isolated from an artisanal Portuguese cheese - Silva, J. (2011)
The main objective of this study was to characterise 8 enterococci strains, isolated from artisanal cheeses of good quality produced in the North of Portugal, including their potential pathogenicity, to determine technologically important characteristics and survival during drying, in order to evaluate the possibility of their use as adjunct starters in cheese production. Phenotypic and genotypic characteristics were used for strains identification. Based on acid production from sugar fermentation and β-galactosidase activity, two strains were identified as Enterococcus durans and 6 strains as E. faecalis. The enterococci strains were further analysed by RAPD-PCR, proteins profile and fatty acids profile. RAPD-PCR was demonstrated to be the most discriminatory typing method. Strain-to-strain variation was observed forthe ability to survive during storage in dried state.